2015
DOI: 10.1007/s00101-015-0077-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Comparison between dexmedetomidine and remifentanil infusion in emergence agitation during recovery after nasal surgery

Abstract: Anesthetic maintenance with either remifentanil or dexmedetomidine infusion until extubation provided a more smooth and hemodynamically stable emergence, without complications after nasal surgery. While remifentanil was superior to dexmedetomidine with regard to avoiding EA, dexmedetomidine was more effective than remifentanil regarding vomiting and pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 33 publications
1
67
0
1
Order By: Relevance
“…In addition, in adult patients undergoing orthognathic surgery, the addition of a single dose of dexmedetomidine (1 μg/kg) to postoperative remifentanil infusion (0.02 μg/kg/min) did not reduce the incidence of EA compared with remifentanil infusion alone [85]. In adult patients undergoing nasal surgery with desflurane anesthesia, dexmedetomidine infusion (0.04 μg/kg/h) from the induction of anesthesia to extubation showed a better EA preventive effect than placebo (saline) infusion; however, it was inferior to remifentanil infusion (0.05 μg/kg/min) [121].…”
Section: α2-adrenoreceptor Agonistsmentioning
confidence: 83%
“…In addition, in adult patients undergoing orthognathic surgery, the addition of a single dose of dexmedetomidine (1 μg/kg) to postoperative remifentanil infusion (0.02 μg/kg/min) did not reduce the incidence of EA compared with remifentanil infusion alone [85]. In adult patients undergoing nasal surgery with desflurane anesthesia, dexmedetomidine infusion (0.04 μg/kg/h) from the induction of anesthesia to extubation showed a better EA preventive effect than placebo (saline) infusion; however, it was inferior to remifentanil infusion (0.05 μg/kg/min) [121].…”
Section: α2-adrenoreceptor Agonistsmentioning
confidence: 83%
“…[ 6 , 13 ] However, despite the direct activation of NMDA receptors by remifentanil, [ 27 ] infusion of remifentanil resulted in smooth awakening from anesthesia and was also effective in decreasing the incidence of EA. [ 4 , 25 ] These findings suggest that potent analgesic activity may be more important in preventing EA than NMDA receptor inhibition. Previous studies support this suggestion.…”
Section: Discussionmentioning
confidence: 97%
“…[ 1 ] In particular, patients undergoing nasal surgery commonly complain of a sense of suffocation due to intranasal packing and manifest agitation during emergence. [ 2 4 ] EA can cause serious problems, such as reoperation due to bleeding of the surgical site, falling out of bed, injury to the patient or medical staff, and unplanned endotracheal tube extubation. [ 5 ] Several pharmacological methods, including opioid (fentanyl, remifentanil), propofol, benzodiazepine (midazolam), α 2 -aderenoreceptor agonist (clonidine, dexmedetomidine), and N -methyl- d -aspartate (NMDA) receptor antagonist (ketamine, magnesium sulfate) administration, have been introduced to mitigate EA.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a previous study showed that the sedative characteristics of dexmedetomidine can suppress the sensitivity of tracheal stimulation, which then results in cough inhibition [23]. However, several studies have shown that a dexmedetomidine infusion, at a rate of 0.4 μg/kg/h during the operation period, did not inhibit cough [24,25]. Park et al [23].…”
Section: Discussionmentioning
confidence: 99%